Intra-Individual Response Variability Assessed by Ex-Gaussian Analysis may be a New Endophenotype for Attention-Deficit/Hyperactivity Disorder - Henríquez-Henríquez, Marcela Patricia; Billeke, Pablo; Henríquez, Hugo; Zamorano, Francisco Javier; Rothhammer, Francisco; Aboitiz, Francisco (Frontiers in Psychiatry, 2015)
Intra-individual variability of Response Times (RTisv) is considered as potential endophenotype for Attentional Deficit/Hyperactivity Disorder (ADHD). Traditional methods for estimating RTisv lose information regarding Response Times (RTs) distribution along the task, with eventual effects on statistical power. Ex-Gaussian analysis captures the dynamic nature of RTisv, estimating normal and exponential components for RT distribution, with specific phenomenological correlates. Here, we applied ex-Gaussian analysis to explore whether intra-individual variability of RTs agrees with criteria proposed by Gottesman and Gould for endophenotypes. Specifically, we evaluated if Normal and/or exponential components of RTs may a) Present the stair-like distribution expected for endophenotypes (ADHD>Siblings>Typically Developing children (TD) without familiar history of ADHD) and b) Represent a phenotypic correlate for previously described genetic risk variants. This is a pilot study including 55 subjects (20 ADHD-discordant sibling-pairs and 15 TD children), all aged between 8 and 13 years. Participants resolved a visual Go/Nogo with 10% Nogo probability. Ex-Gaussian distributions were fitted to individual RT data and compared among the three samples. In order to test whether intra-individual variability may represent a correlate for previously described genetic risk variants, VNTRs at DRD4 and SLC6A3 were identified in all sibling pairs following standard protocols. Groups were compared adjusting independent general linear models for the exponential and normal components from the ex-gaussian analysis. Identified trends were confirmed by the non-parametric Jonckheere-Terpstra test. Stair-like distributions were observed for μ (p=0.036) and σ (p=0.009). An additional “DRD4-genotype” X “clinical status” interaction was present for τ (p=0,014) reflecting a possible severity factor. Thus, Normal and exponential RTisv components are suitable as ADHD endophenotypes.